The Case of the Reasonable Hypothetical Sex Worker - Haak, Debra M. (Alberta Law Review, 2022)
This article critically considers the expanded use of reasonable hypotheticals in challenging the constitutionality of criminal offences under section 7 of the Canadian Charter of Rights and Freedoms (Charter). The author consolidates concerns raised by judges and scholars over use of the device and explains how these concerns are amplified in the first two constitutional challenges to three of Canada’s new criminal prostitution laws with potentially significant consequences for constitutional limitations on what can and cannot constitute a crime. The reasonable hypothetical is a device originally used by courts to evaluate the constitutionality of mandatory minimum sentences under section 12 of the Charter based on the circumstances of a reasonable hypothetical offender, rather than those of the actual offender before the court. Judges later expanded the use of the device to evaluate the constitutionality of criminal offences under section 7 based on the circumstances of a reasonable hypothetical accused, rather than those of the actual accused before the court. However, the process through which constitutionality is evaluated differs, raising distinct concerns about the use of hypotheticals in evaluating the constitutionality of criminal offences that have largely gone unexamined and unacknowledged. Concerns raised by judges and scholars about the use of reasonable hypotheticals fall into three categories: (1) the “air of unreality,” where the rights violation at issue does not arise on the facts of the case before the court; (2) the nature and scope of evidence that can, should, or must be before the court in cases where the device is used; and (3) the appropriate remedy where an impugned law applies in a constitutional manner to the offender or accused before the court, but in an unconstitutional manner in hypothetical circumstances. Each of these categories of concern is aggravated in the first two constitutional challenges to some of Canada’s new criminal commodification offences; the way hypotheticals are used in section 7 cases obscures the experiences of victims and complainants and allows courts to adjudicate constitutionality and remedy constitutional breaches based solely on hypotheticals and expert evidence. The author suggests that if courts continue to allow accused in criminal proceedings to use reasonable hypotheticals to challenge the constitutionality of offences under section 7 of the Charter, they undertake their evaluation of constitutionality with the benefit of adjudicative fact evidence about the circumstances of the case before them, to directly address how rights, interests, and values in tension with those of the hypothetical rights claimant may be relevant to a potential section 1 justification and tailor a remedy that meaningfully attends to the experiences of victims and complainants.